Influence of calcium‐based desensitizing toothpastes on the bonding performance of universal adhesive. Issue 4 (28th December 2022) - Wang, Silin; Meng, Yuchen; Zhang, Yuchen; Huang, Fan; Teng, Rui; Lu, Yi; Li, Ang; Sun, Junyi; Pei, Dandan
Abstract: The study evaluated the effect of calcium‐based desensitizing toothpastes on the dentinal tubule occlusion and its influence on the dentin bond strength of universal adhesive. Mid‐coronal dentin samples were prepared for hypersensitivity model and treated by the following calcium‐based desensitizing toothpastes: no treatment (Control), Clinpro (fTCP), Pro‐Relief (Pro‐Argin), and Repair & Protect (Novamin). Single Bond Universal adhesive was applied in self‐etch or etch‐and‐rinse mode. The dentinal tubule occlusion and adhesion interface were evaluated under scanning electron microscope (SEM). A double‐fluorescence technique was used to examine interfacial permeability under confocal laser scanning microscopy (CLSM). The micro‐tensile bond strength (μTBS) was employed, followed by the fracture interface observation. SEM showed the toothpastes occluded dentinal tubules, and the occlusion exhibited stability against acid and abrasion. Hindered resin infiltration was observed in the adhesion interface after desensitization. CLSM showed more water permeation within or under the adhesion interface in etch‐and‐rinse mode than self‐etch mode. Desensitization decreased the μTBS in self‐etch mode. When using etch‐and‐rinse mode, the desensitized samples presented similar μTBS to the control group. No difference in μTBS was found between the two bonding modes, except for the control group. Calcium‐based desensitizing toothpastes can effectively occlude the exposed dentinal tubules with acid‐resistant and abrasion‐resistant stability. The desensitization reduced the dentin bond strength of the universal adhesive system in self‐etch mode but did not affect the bond strength of etch‐and‐rinse mode. Abstract : Schematic diagram of the experimental process: desensitization altered dentin surface property and adhesive performance.